Unisphere, New York World's Fair 1964-1965 (Dexter Press, Inc.)
The Court of Peace with the Unisphere in the background. The Unisphere is the largest globular structure ever built by man. The National Arts Club has cited the result as "One of the most outstanding achievements in structural sculpture of this decade."